The right of diocesan clergy to the protection of their intimacy versus their right to a decent livelihood. Reflections on the final judgment of the Supreme Tribunal of the Apostolic Signatura - Adamczyk, Jerzy (Prawo Kanoniczne, 2024)
The right of diocesan clergy to the protection of their intimacy versus their right to a decent livelihood. Reflections on the final judgment of the Supreme Tribunal of the Apostolic Signatura The subject of this article is the issue of the right of diocesan clergy to protect their intimacy vis-à-vis their right to a decent livelihood. The reflections are based on the final judgment of the Supreme Tribunal of the Apostolic Signatura. The aim of the study was to show and explain, on the basis of specific provisions, the legal grounds for the protection of one's intimacy and the right to a decent livelihood, and to show the correlation between these rights. This research objective was realised by means of a description and a thorough analysis of the applicable provisions and texts of the ecclesiastical magisterium, especially the aforementioned judgment of the Signatura. The analysis of the aforementioned sources allowed several main conclusions to be drawn. Firstly, it was clarified and justified that clergy, as long as they have not lost their clerical state, have a right to a decent livelihood. Secondly, it was concluded that the right to protect one's intimacy is an important right of everyone, not only the baptised. It is particularly guaranteed in the legal order of the Church. This right must not be violated by anyone, no one can be forced to give up this right; on the contrary, everyone must respect it. Thirdly, it has been shown that as long as a clergyman has not lost his clerical state, he has the right to a decent livelihood, but also the right to protect his intimacy.